ANALISIS PENDAPATAN DAN FAKTOR – FAKTOR YANG MEMPENGARUHI KEUNTUNGAN USAHATANI BAWANG MERAH DI KECAMATAN GUNUNG ALIP KABUPATEN TANGGAMUS - Nurul Sarwinda; Bustanul Arifin; Maya Riantini (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analysis income and factors affecting profitability of red onion farming. This research was conducted in Gunung Alip Subdistrict, Tanggamus District.  This study used a survey method, while data were collected by census of 30 red onion farmers in the study area. Data collection was carried out from March to April 2019. The first objective was to find out the income of red onion farming using R-C ratio analysis, while the second objective was to find out the factors affecting the profit of red onion farming using the Cobb-Douglas UOP profit function analysis (Unit Output Price). The results showed that income over cash costs is IDR 63,723,312.16 per planting season/ha and income over total costs is IDR 54,013,048.10 per planting season/ ha.  R/C value of cash costs is 2.51 and R/C of total costs is 2.04, so that red onion farming is profitable.  Factors affecting the profitability of red onion farming are the price of red onion seeds (X1), labor costs (X8), and land size (Z1). Key words: farming, income, red onion, profit.